Rhetorical Coherence and Eco-Theological Meaning in Qur’anic Water Verses: A Disciplined Semitic Rhetorical Analysis - Aqdi Rofiq Asnawi; Mahmud Rifaannudin; Deki Ridho Adi Anggara; Oky Ayu Agustin (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
Too often, eco-theological readings of Qur’anic water verses outrun the text—because structural claims are made without a disciplined, transparent, and auditable method. This article examines whether Semitic Rhetorical Analysis (SRA) can serve as an audit-able tool for reading Qur’anic water passages in a way that disciplines ecological inference. Focusing on Q 23:18–19 and Q 25:48–49, it asks how rhetorical segmentation and parallelism clarify the internal logic of the verses beyond atomistic citation. Using qualitative library-based research, the study applies Meynet’s SRA procedure (segmenting the text, identifying correspondences, and mapping inter-unit relations) and then compares the resulting structure with thematic Qur’anic-ecological readings on water, balance (mīzān), and stewardship (khalīfah). The analysis shows that SRA makes visible a coherent argumentative sequence—sending down water, settling it, and directing its benefits—that frames water as an entrusted measure rather than a merely descriptive sign. It also constrains interpretive overreach by requiring each ecological claim to be traceable to a demonstrable textual relation, while still supporting an ethic of restraint and care. Overall, the article indicates that rhetorical-structural analysis can strengthen eco-tafsīr by providing a replicable pathway from textual structure to ethical inference.